Analisis Kinerja Karyawan pada Hana Bank Gatot Subroto Jakarta - Maulana, Agung (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2023)
Performance appraisal is needed by every business organization to determine the results or level of success of employees. Through performance appraisal, the results can be used for purposes including human resource decisions, evaluation, and feedback. Positive feedback will show that employees feel valued from their work and can tell what things need to be improved from them so that employees will improve their performance, the purpose of this research is to find out how employees work at Hana Bank, this research uses the method model qualitative approach with descriptive analysis techniques, employee performance at Hana Bank Gatot Subroto Jakarta still has obstacles in maximizing employee performance such as: Absences, employee absences at Hana Bank Gatot Subroto Jakarta still show a bad percentage, this greatly affects the performance and discipline of employees in carrying out duties and responsibilities, then problems in communication that result in non-delivery of accepted job duties and responsibilities. There are findings that the work quality of Hana Bank Gatot Subroto Jakarta employees is very good, where Hana Bank Gatot Subroto Jakarta always improves good facilities to increase and maintain employee satisfaction and quality to improve employee performance.